Pemanfaatan Minyak Jelantah sebagai Bahan Bakar Alternatif Ramah Lingkungan pada Kompor Rumah Tangga - Suwarno, Djoko; Wiwien Widyastuti; Bernadeta Wuri Harini; Haris Sriwindono; Lukas Purwoto (Retii, 2024)
Used cooking oil, which is often thrown away after use, can have a negative impact on the environment if not managed properly. Through a community service program implemented in Sidomoyo Village, Godean, Sleman, efforts were made to convert used cooking oil into biodiesel as an environmentally friendly alternative fuel for household stoves. This program aims to empower the community by providing knowledge and skills in processing used cooking oil, so that this waste can be reused productively and reduce environmental pollution. The process of converting used cooking oil into biodiesel involves a simple method that can be implemented by village communities at an affordable cost. The use of biodiesel in household stoves is expected to be an alternative energy solution that is economical and environmentally friendly, as well as supporting efforts to reduce domestic waste. The results of this activity show the enthusiasm of the community in adopting this technology, as well as increasing awareness of the importance of managing used cooking oil waste. It is hoped that this program can become a model of curiosity that is implemented in other villages.